Effect of Mechanical Interaction between Clothing and Body on Skin Blood Flow (Journal of Fiber Bioengineering and Informatics, 2012)
The mechanical interaction between the human body and foundation wear, which consists of normal load(pressure) and tangential load (shear), has a complicated influence on human physiological activities.In this study, five female subjects were asked to lay supine still, pressure loads of 20 mmHg and 40mmHg and two levels of shear loads were exerted on the shank respectively, and the blood flow of skinundergoing loading was measured by using Advance Laser Blood Flowmeter. The results obtained wereas follows: the low pressure could promote the skin blood flow; the shear load was effective in reducingthe skin blood flow; little shear added to the pressure had important role on reducing the skin bloodflow.
Keywords: Foundation Wear; Pressure; Shear; Skin Blood Flow